2021
DOI: 10.1097/cm9.0000000000001617
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and independent predictors of mortality in patients presenting to emergency departments with acute heart failure in Beijing: a multicenter cohort study with a 5-year follow-up

Abstract: Background: Acute heart failure (AHF) is the most common disease in emergency departments (EDs). However, clinical data exploring the outcomes of patients presenting AHF in EDs are limited, especially the long-term outcomes. The purposes of this study were to describe the long-term outcomes of patients with AHF in the EDs and further analyze their prognostic factors. Methods: This prospective, multicenter, cohort study consecutively enrolled 3335 patients with AHF who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Results of DBP in patients with AHF and in the real‐world setting were generally consistent with those seen in several studies 44,45 . Elevated SBP has been shown to prolong survival time in patients with AHF 46 ; however, we found that DBP was more relevant to the risk of all‐cause mortality than SBP, suggesting that we should consider DBP in addition to SBP in further studies regarding the prognosis or clinical prediction models in patients with AHF.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results of DBP in patients with AHF and in the real‐world setting were generally consistent with those seen in several studies 44,45 . Elevated SBP has been shown to prolong survival time in patients with AHF 46 ; however, we found that DBP was more relevant to the risk of all‐cause mortality than SBP, suggesting that we should consider DBP in addition to SBP in further studies regarding the prognosis or clinical prediction models in patients with AHF.…”
Section: Discussionsupporting
confidence: 87%
“…Results of DBP in patients with AHF and in the real-world setting were generally consistent with those seen in several studies. 44,45 Elevated SBP has been shown to prolong survival time in patients with AHF 46 ; however, we found that DBP was more relevant to the risk of all-cause mortality than SBP, suggesting that we should consider DBP in addition to SBP in further studies regarding the prognosis or clinical prediction models in patients with AHF. While the exact mechanism by which higher DBP improves survival outcomes is yet to be established, it is presumed that the haemodynamic ability to elevate blood pressure (BP) and tolerate an increased afterload represents preserved cardiac function, and thus may correlate with the extent and severity of HF.…”
Section: Discussionmentioning
confidence: 73%
“…Among the remaining 4,979 papers, a series of publications unrelated to heart failure research, such as conference studies and case reports, were excluded, and 131 articles were obtained. A re-screening of data types and outcome indicators of blood urine nitrogen was performed on the 131 articles, and 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) of them were finally included (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…These abnormal clinical features include long duration, high mortality, and poor prognosis. [ 1 ] The state of HF is characterized by recurrence, slow progression, and progressive worsening. Epidemiological studies in China found that the incidence of HF in subjects >65 years of age was 6–10%, while at the age of 35–64 years, the incidence was 0.9%.…”
Section: Introductionmentioning
confidence: 99%